Multifuncionalidade e intersubjetividade em construções concessivas: uma análise em ocorrências do português contemporâneo do Brasil - Zamproneo, Silvana [UNESP] (2014)
In this dissertation we investigate concessive constructions in contemporary Brazilian Portuguese considering that concessive relation is a case of complex clause combination that deserves attention in the grammar of natural languages. The theoretical basis for the exam is the functional theory of language, which reformulates the rigid distinction between traditional subordination and coordination, observing the textual and discursive level and describing clausal combination with respect to syntax, semantics and pragmatics. Valuable tenets from Cognitive Linguistics, permeated by analytical principles of Functional Linguistics, are invoked and considered to clarify and drive the analysis of concessivity in order to deal with the category of intersubjectivity that, by hypothesis, is crucially intricate to the expression of concessivity. The corpus is composed of concessive constructions from both spoken and written contemporary Brazilian Portuguese and even though it is not our aim to deal with the differences between these modalities of language use, our hypothesis is that the complexity of the concessive relation is instantiated differently in each modality. The goals of this research comprise: the investigation of the concessive category in language; the verification, in language use, of logical-semantic values of this category; the verification, in language use, of discursive-pragmatic values of concessive constructions; the verification, in language use, of imminently argumentative functions with the expression of concessivity, articulated with the expression adversativity; the verification, in language use, supported by cognitive principles, of concessive constructions that distance from the prototypical local-semantic configuration of concessivity; the verification, in language use, of the involvement of intersubjectivity in the expression of concessivity, considering its interactive and dialogical expression. These goals have ...